Health Education and Assistance as an Empowerment Model in Improving the Quality of Family Latrines - Omo Sutomo; Yayah Rokayah; Wasludin Wasludin (Poltekita : Jurnal Ilmu Kesehatan, 2023)
There are still many areas in Indonesia that do not have adequate access to sanitation facilities, including family latrines. Especially in rural and suburban areas, sanitation infrastructure is poor, so people still rely on open defecation practices. This research aims to determine the effect of Health Education through assistance and Community Empowerment in increasing the use of family latrines that fulfil sanitation requirements. The research design uses a quasi-experiment with a multiple time series design (pre-test and post-test with control group design). The research was conducted in the working area of ​​the Mekarsari Public Health Center, Lebak-Banten Regency. The intervention group comprised 88 families, and the control group had 88 families. The test used t-test statistical analysis to determine the differences before and after treatment about the quality of family latrines. The study results showed an increase in the average family latrine quality score and minimum and maximum score in the control group after being given health education about healthy latrines. There was a significant increase in the average family latrine quality score and minimum score in the intervention group after being given health education about healthy latrines. There was a difference increase in the deviation (after-before) in the family latrine quality score between the control group (1.51) and the intervention group (3,30). Likewise, the minimum and maximum scores were higher than the difference in family latrine quality scores in the intervention group. Statistically, there is a difference in the average difference (after-before) in the latrine quality scores between the control group and the intervention group. In other words, there is an influence of the community empowerment model for the quality of family latrines (p=0,000).